Evaluation of Deaf Employees' Work Ability on Cognitive, Affective and Psychomotor Aspects in a Cigarette Factory PT. Cakra Guna Cipta Malang Regency - Ratnayanti, Rahajeng; Efendi, Mohammad; Hastuti, Wiwik Dwi (East Asian Journal of Multidisciplinary Research, 2024)
Special Schools are formal institutions that are responsible for the quality of human resources for deaf people so that they can be accepted in the job market, especially labor-intensive industries. The learning process is expected to produce quality human resources in cognitive, affective and psychomotor aspects that influence work ability. This work ability will have an impact on the level of satisfaction of the company that employs them. This research aims to evaluate the work abilities of deaf people in cognitive, affective and psychomotor aspects. This research uses a qualitative exploratory case study methodology with an instrumental case study research design type. The research results prove that deaf employees who work at the Cakra Cigarette Factory must be able to communicate both orally and in writing. They generally have low literacy skills, poor receptive and expressive communication skills, resulting in a lack of understanding of the work contract text. In terms of discipline, they are much more disciplined than normal employees. Socially, they are able to establish good relationships with fellow colleagues. In terms of work skills, deaf employees have higher productivity than normal employees.